Cognitive Function in Children with Epilepsy - Putra, Bayu Pratama; Triono, Agung; Susilawati, Dwi (Journal of Nepal Paediatric Society, 2019)
Introduction: Epilepsy is a worldwide and common child health problem. One of its complications is cognitive impairment that will impact on children’s cognitive development and quality of life. The objective of this study is to find out whether epilepsy affects cognitive function in children. Material and Methods: This was a cross-sectional descriptive study using secondary data from medical records. We collected data from children with epilepsy from 2004 until 2014 that have been actively managed in the Growth and Development Clinic, Sardjito General Hospital, Yogyakarta, Indonesia. Cognitive function referred to low IQ score that was gained from patients’ data. We analyzed the data using Fischer’s exact and two-sample Kolmogorov-Smirnov test methods. Results: Among 40 data samples, there were 19 patients (42.5%) with cognitive impairment (IQ < 70) and 21 patients (57.5%) without cognitive impairment (IQ ≥ 70). There were twenty-five patients examined by the Stanford-Binet IQ test, which found 15 patients with cognitive impairment. In fifteen patients who were examined with the WISC test, we found more children with epilepsy without cognitive impairment (11 patients). Comorbidity with neuro-developmental disorder significantly affected cognitive impairment in children with epilepsy (p value = 0.034, 95% CI 1.08-21.76). Conclusions: More children with epilepsy without cognitive impairment were found. Further studies are needed with larger number of samples utilizing a prospective study design to better determine the association of epilepsy in children and cognitive impairment.